Body size characteristics and polymorphism in GH and GHRH genes of Simeulue Buffalo of Aceh, Indonesia - KARTINI ERIANI; RAHMI RAHMI; IKHWAN JAMIL; ROSNIZAR ROSNIZAR; AL AZHAR (Biodiversitas Journal of Biological Diversity, 2019)
Eriani K, Rahmi R, Jamil I, Rosnizar R, Azhar A. 2019. Body size characteristics and polymorphism in GH and GHRH genes of Simeulue Buffalo of Aceh, Indonesia. Biodiversitas 20: 236-242. This study was done to determine body size characteristics, to identify the presence of polymorphism in the GH/MspI and GHRH/HaeIII genes, and to analyze the relationship between GH and GHRH gene polymorphisms to body size characteristics in Simeulue buffalo. Experimental animals used were 45 Simeulue buffalo randomly sampled from three subdistricts, i.e., Salang, Alafan and Simeulue Cut, fifteen from each subdistrict. Body size characteristics measured were withered height, body length, chest circumference, chest depth, and hip height. A 5 mL whole blood was collected from fifteen out of forty five by using EDTA as an anticoagulant. Extraction of genomic DNA and analysis of GH/MspI and GHRH/HaeIII polymorphisms was done using GeneAid DNA extraction kit and polymerase chain reaction-restriction length fragment polymorphism (PCR-RFLP) method, respectively. The data of body size characteristics which includes mean value, standard deviation, and coefficient of variation were analyzed descriptively. The molecular data represented by DNA banding pattern was used to calculate allele and genotype frequencies, expected (He) and observed (Ho) heterozygosities, and Hardy-Weinberg equilibrium. The relationship between genotype and body size characteristic was analyzed using t-test. The results showed that coefficient of variation in body size characteristics was low, ranging from 5.39-16.06% in the age category of 4-6 years old and ranging from 5.25-11.27% in the age category of 2- 4 years old. The results of the molecular analysis indicated that GH/MspI locus was monomorphic by the presence of one (+/+) genotype. GHRH/HaeIII locus was polymorphic as shown by the presence of 3 genotypes namely AA (0.13), AB (0.80) and BB (0.07). Expected heterozygosity (0.80) was higher than observed heterozygosity (0.49). The frequency of GHRH/HaeIII agreed with Hardy Weinberg equilibrium. GHRH/HaeIII polymorphism did not significantly influence (P>0.05) body size characteristics of Simeulue buffalo.